Prussian Blue Analogues as Promising Thermal Power Generation Materials. Issue 10 (3rd August 2018) - Fukuzumi, Yuya; Amaha, Kaoru; Kobayashi, Wataru; Niwa, Hideharu; Mortitomo, Yutaka
Abstract: The thermal coefficient ( α =d V /d T ) of redox potential ( V ) enables an efficient thermal power generation using waste heat. Actually, a battery‐type thermocell, which consists of two kinds of redoxable solids with different α as anode and cathode, is demonstrated to produce electric energy in thermal cycles. To fabricate high performance device, α is systematically investigated in three kinds of Prussian blue analogues (PBAs), Na x Co[Fe(CN)6 ]0.71 (abbreviated as NCF71), Na x Co[Fe(CN)6 ]0.90 (NCF90) and Na x Mn[Fe(CN)6 ]0.83 (NMF83), against the Na + concentration ( x ). NCF90 shows the highest positive α (=1.4 mV K −1 ) in the lower‐lying plateau while NMF83 shows the highest negative α (=−0.4 mV K −1 ) in the lower‐lying plateau. In addition, the NCF90/NMF83 thermocell produces 5.5 meV/NCF90 in the initial cycle between T L (=286 K) and T H (=313 K). The thermal efficiency ( η =2.3 %) reaches 27 % of the Carnot efficiency ( η carnot =8.7 %). Thus, PBAs are promising materials for thermal power generation. Abstract : Thermal coefficient (α) od redox potential enables an efficient thermal power generation using its difference (Δα) between cathode and anode. The magnitude of α in Mn− and Co‐PBAs are carefully determined against Na + concentration (x). NCF90 shows the highest positive SEC (=1.4 mV K −1 ) while NMF83 shows the highest negative SEC (=−0.4 mV K −1 ). The NMF83/NCF90 thermocell shows high efficiency thermal power generation (η=2.3 %) between 286 K (=TL ) and 313 K (=TH ).